Acute liver failure: The medical management - Chandra Kant Pandey; Monika Singh; Sumi Saxena; Mohammad Danish; Ashish Khanna; Tanushree Srivastava (Wolters Kluwer -Medknow Publications, 2024)
Acute liver failure (ALF) is a clinical condition caused by multiple factors, such as drugs, viruses, and vascular causes. It is defined as coagulopathy and encephalopathy occurring in a time span of <6 months in a healthy patient with no preexisting liver disease. ALF is classified as, hyperacute, acute, and subacute on the basis of the duration of development of encephalopathy since the initial appearance of jaundice. The management of ALF comprises the treatment of hepatic and extrahepatic organ system dysfunction. The early recognition and treatment of raised intracranial pressure are the prerequisite for better neurologic outcome and survival. The main pathogenetic factor in the development of ALF is ammonia, but the role of newer ammonia-lowering agents is not well established. Once intracranial hypertension sets in, hypertonic saline and mannitol are the first-line therapy. Only liver transplants have been promising to be effective in patients with poor prognostic factors. Thus, it is vital to identify the complications and appropriate usage of different prognostic models in segregating the patients who require medical management or liver transplant, which is the mainstay of therapy.